Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Kecamatan Beji Kota Depok - Muhammad Ridwan Kurniawan; Ade Sri Mulyani (Universitas Kristen Indonesia Toraja, 2024)
Beji Sub-district Office is 1 of 11 sub-districts in the city of Depok which has the task of assisting the Mayor in coordinating the administration of general government affairs, government affairs in the field of community empowerment and urban villages as well as the delegation of part of government affairs in other fields. The purpose of this study was to determine the effect of work discipline and work environment on the performance of Beji District employees in Depok City. The research was conducted for 3 months (April - June 2024). Data collection methods are through interviews, questionnaires and observations distributed to 58 respondents. The analysis method is quantitative statistics. Data analysis includes instrument quality tests consisting of validity and reliability tests, classical assumption tests, t tests and F tests. The results of this study indicate that the Work Environment partially has a positive and significant effect on the Performance of Employees of the Beji District Office. Work Discipline partially has a positive and significant influence on the Performance of Employees of the Beji District Office. Work Environment and Work Discipline simultaneously have a positive and significant influence on the Performance of Employees of Beji Subdistrict Office. The implication of the results of this study is that providing a good work environment and work discipline will improve employee performance..